Tailoring lifestyle interventions to low socio-economic populations: a qualitative study - Nia Coupe; Sarah Cotterill; Sarah Peters (BMC, 2018)
Abstract Background People living in deprived areas are more likely to be overweight or obese, have poorer health outcomes, and tend to benefit less from interventions than those from more affluent backgrounds. One approach to address such health inequalities is to tailor existing interventions to low socio-economic populations, yet there is limited evidence to inform their design. This study aims to identify how best to tailor lifestyle interventions to low socio-economic populations to improve outcomes. Methods Following direct observations of community-run weight loss groups, we interviewed 11 group facilitators and 14 service users from a health improvement service in a low socio-economic area in the North West of England. Audio-recorded interviews were transcribed verbatim and analysed thematically. Results We identified two overarching themes within the data. The first theme, managing diversity, included challenges faced in delivering a generic intervention to a diverse population in terms of knowledge, language and literacy skills, and cultural diversity. The second theme incorporated all issues relating to the environment, such as cost, access and availability of food and leisure facilities, and 'life gets in the way'. Conclusions Tailoring interventions for this population is necessary, and more attention is needed to develop ways to ensure service providers and users engage with behaviour change techniques such as goal setting, rather than focusing on information provision alone. Interventions should also be mindful of cost, cultural diversity, and language and literacy barriers, as well as potential for disengaging this hard to reach population.